Heat and Mass Transfer in Reduction Zone of Sponge Iron Reactor. (7th August 2011) - Alamsari, Bayu; Torii, Shuichi; Trianto, Azis; Bindar, Yazid
Abstract : Numerical prediction is performed on reduction zone of iron ore reactor which is a part of counter current gas-solid reactor for producing sponge iron. The aim of the present study is to investigate the effect of reduction gas composition and temperature on quality and capacity of sponge iron products through mathematical modeling arrangement and simulation. Simultaneous mass and energy balances along the reactor lead to a set of ordinary differential equation which includes kinetic equations. Kinetic equations of reduction of hematite to iron metal, methane reforming, and water gas shift reaction are taken into account in the model. Hydrogen and carbon monoxide are used as reduction gas. The equations were solved by finite element method. Prediction shows an increase in H2 composition while an attenuation of CO produces higher metallization degree. Metallization degree is also increased with an increase in gas inlet temperature. It is found that reduction gas temperature over 973°C (1246 K) is not recommended because the formation of sticky iron will be initiated.